Multi-dimensionality of chronic pain of the oral cavity and face - Zakrzewska, Joanna M (Springer, 2013)
Orofacial pain in its broadest definition can affect up to 7% of the population. Its diagnosis and initial management falls between dentists and doctors and in the secondary care sector among pain physicians, headache neurologists and oral physicians. Chronic facial pain is a long term condition and like all other chronic pain is associated with numerous co-morbidities and treatment outcomes are often related to the presenting co-morbidities such as depression, anxiety, catastrophising and presence of other chronic pain which must be addressed as part of management . The majority of orofacial pain is continuous so a history of episodic pain narrows down the differentials. There are specific oral conditions that rarely present extra orally such as atypical odontalgia and burning mouth syndrome whereas others will present in both areas. Musculoskeletal pain related to the muscles of mastication is very common and may also be associated with disc problems. Trigeminal neuralgia and the rarer glossopharyngeal neuralgia are specific diagnosis with defined care pathways. Other trigeminal neuropathic pain which can be associated with neuropathy is caused most frequently by trauma but secondary causes such as malignancy, infection and auto-immune causes need to be considered. Management is along the lines of other neuropathic pain using accepted pharmacotherapy with psychological support. If no other diagnostic criteria are fulfilled than a diagnosis of chronic or persistent idiopathic facial pain is made and often a combination of antidepressants and cognitive behaviour therapy is effective. Facial pain patients should be managed by a multidisciplinary team.